Report of the Working Group on Labour Laws and Other labour regulations for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission Government of India, 2001)
The Tenth Five Year Plan (2002–2007) Working Group on Labour Laws examined reforms aimed at enhancing employment generation, worker protection, and effective implementation of labour legislation in India. Key recommendations include modernizing labour laws to address technological change, globalization, and sector-specific needs, such as Information Technology, Special Economic Zones, and Small Scale Industries, with simplified compliance through self-certification. The report emphasizes strengthening social security for retrenched workers through enhanced compensation and schemes like Ashraya Bima Yojana. Additionally, it advocates for inspection reforms, quasi-judicial tribunals for expedited dispute resolution, and practical enforcement strategies to balance regulatory compliance with economic growth. Overall, the report presents a framework to create a flexible, efficient, and socially secure labour market that supports industrial competitiveness while safeguarding workers’ rights.
Government of India Planning Commission October-2001
Keywords: Labour Laws; Tenth Five Year Plan; Employment Generation; Social Security; Retrenched Workers; Self-Certification; Small Scale Industries; Industrial Disputes; Labour Law Modernization; Sector Flexibility; Worker Protections; Regulatory Framework